2020
DOI: 10.3390/antibiotics9020055
|View full text |Cite
|
Sign up to set email alerts
|

A 28 Day Clinical Assessment of a Lactic Acid-containing Antimicrobial Intimate Gel Wash Formulation on Skin Tolerance and Impact on the Vulvar Microbiome

Abstract: While intimate feminine hygiene products are widely used as part of daily cleansing routines, little is known about how these products impact the vulvovaginal area and its microbiome stability. This 4 week clinical study assessed tolerance of a novel gel wash containing lactic acid (pH 4.2) for external daily use when used on the external genital area and its effects on skin moisturization, vulvar skin pH, and the vulvar microbiome. After a 7 day pre-study conditioning period, 36 healthy females in three balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
19
0
6
Order By: Relevance
“…A previous study has shown that application of LGR-1 to the vagina can stimulate antimicrobial peptides [42], making it a good choice for this type of application. An advantage of applying live bacteria rather than compounds such as lactic acid [43] is that the probiotic strains can adapt to the environment and produce other substances important to health maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that application of LGR-1 to the vagina can stimulate antimicrobial peptides [42], making it a good choice for this type of application. An advantage of applying live bacteria rather than compounds such as lactic acid [43] is that the probiotic strains can adapt to the environment and produce other substances important to health maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of skin pH has been demonstrated to cause detachment of commensal microbiota ( Lambers et al, 2006 ). An antibacterial intimate wash formulated with lactic acid was recently demonstrated to stabilize the pH of the vulvar skin, while causing no negative impacts on the richness or diversity of the microbiome ( Bruning et al, 2020 ). When formulating with organic acids, the pH of the formulation and the pKa of the acid must be considered.…”
Section: Synergistic Role Of Soap Ingredients In Removal And/or Inactivation Of Pathogensmentioning
confidence: 99%
“…Based on the anatomical and physiological aspects of the intravaginal drug administration route, the optimal intravaginal formulation should (a) enable the delivery of low molecular weight hydrophilic or lipophilic compounds as they have the highest absorption rates due to their transport mechanism; (b) be partially water-soluble due to the aqueous properties of the vaginal discharge; (c) be easy to administer; (d) have bioadhesive properties in order to prevent washing-out from the vaginal lumen [ 14 , 44 ]. Another influential property of an intravaginal drug formulation is its osmolarity.…”
Section: Technological Aspects Of Vaginal Formulations Developmentmentioning
confidence: 99%